2018
DOI: 10.1021/acs.jmedchem.8b00589
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Insights for Small Molecule Inhibition of Macrophage Migration Inhibitory Factor

Abstract: Macrophage migration inhibitory factor (MIF) is an upstream regulator of the immune response whose dysregulation is tied to a broad spectrum of inflammatory and proliferative disorders. As its complex signaling pathways and pleiotropic nature have been elucidated, it has become an attractive target for drug discovery. Remarkably, MIF is both a cytokine and an enzyme that functions as a keto-enol tautomerase. Strategies including in silico modeling, virtual screening, high-throughput screening, and screening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 144 publications
1
52
0
Order By: Relevance
“…In addition, the effect of injecting foreign antigens in the form of subcutaneous ASIT will induce an innate immune response . Stimulation of the innate immune system by lipopolysaccharide and other ligands such as allergens causes a rapid release of MIF from cells and tissues . This antigenic stimulation also can induce dendritic cells to increase production of IFNα, thus inducing macrophages to release MIF .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effect of injecting foreign antigens in the form of subcutaneous ASIT will induce an innate immune response . Stimulation of the innate immune system by lipopolysaccharide and other ligands such as allergens causes a rapid release of MIF from cells and tissues . This antigenic stimulation also can induce dendritic cells to increase production of IFNα, thus inducing macrophages to release MIF .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage migration inhibition factor (MIF) is an immunoregulatory cytokine that through interactions with its receptor CD74, recruits and activates macrophages at inflammatory loci . The most important source of MIF is T‐helper 2 cells (Th2), where MIF is essential for T‐cell activation, but other sources include macrophages, eosinophils, epithelial cells, endothelial cells and keratinocytes.…”
Section: Introductionmentioning
confidence: 99%
“…These include the dopachrome analog MIF inhibitors NAPQI, OXIM-11, and DEBIO-1036; two oxazoline derivatives CPSI-2705 and CPSI-1306; the isoxazoline compounds ISO-1, ISO-66, and ISO-92 [77]; and biaryltriazole, pyrazole, and benzoxazol-2-thione [77]. MIF inhibitors identified with in silico methods are the compound Z-590 that inhibits several MIF functions, benzoxazol-2-thione, and ORITA-13; potent inhibitors of the tautomerasic action are 2-oxo-4-phenyl-3-butanoate, phenylpyrimidines, acetaminophen analogs, epicatechins, and the 4-iodo-6-phenylpyrimidine (4-IPP), mainly known for its ability to target both MIF and DDT [15]; a selection of approved drug (ibudilast, ebselen, and iguratimod) [77]; natural products (benzyl isothiocyanate, L/D-thyroxine, ellagic acid, epoxyazadiradione, spirohexenolide-A, a sulfonade organic acid, p425, and a novel isocoumarin compound SCD-19) [76][77][78]. 1,2,3-triazole derivatives have been reported as MIF inhibitors [74].…”
Section: The Emerging Class Of Single and Dual Inhibitors Of Mif Andmentioning
confidence: 99%
“…In particular, a recent Phase II study has shown promising effects of ibudilast in patients with multiple sclerosis [81][82][83]. Other drugs that are being repurposed as MIF inhibitors are ebselen and iguratimod [77].…”
Section: Repurposed Drugs As Mif Inhibitors the Case Of Ibudilastmentioning
confidence: 99%
“…Although originally recognized as macrophage migration inhibitor, the cytokine is known to induce secretion of proinflammatory cytokines including TNF‐α, IL‐1, 6, 8, and 12, recruit various inflammatory cells, and upregulate expression of adhesion molecules on monocytes and endothelial cells . Several small‐molecule inhibitors of MIF have been investigated for cancer therapy, inflammatory, and immune disorders . An oral small‐molecule inhibitor of MIF, CSPI‐1306, was found to reduce blood glucose, TNF‐α, and IL‐6 levels in type 2 diabetic outbred Institute of Cancer Research (ICR) mice .…”
Section: Cytokines and Therapies That Modulate Their Activitymentioning
confidence: 99%